2012
DOI: 10.1016/j.neuroscience.2012.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dependence of cysteine protease activation following excitotoxic hippocampal injury

Abstract: Excitotoxic insults can lead to intracellular signaling cascades that contribute to cell death, in part by activation of proteases, phospholipases, and endonucleases. Cysteine proteases, such as calpains, are calcium-activated enzymes which degrade cytoskeletal proteins, including microtubule-associated proteins, tubulin, and spectrin, among others. The current study used the organotypic hippocampal slice culture model to examine whether pharmacologic inhibition of cysteine protease activity inhibits N-methyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…The DHA concentrations used, reported to sustain neuronal viability in primary brain cultures [46] , border physiological values for n-3 fatty acids [47] . Slices then were treated as described below with propidium iodide (PI), a fluorescent dye selectively accumulated by dying and dead neurons in organotypic brain slices [48] , [49] , or pooled for immunoblot analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The DHA concentrations used, reported to sustain neuronal viability in primary brain cultures [46] , border physiological values for n-3 fatty acids [47] . Slices then were treated as described below with propidium iodide (PI), a fluorescent dye selectively accumulated by dying and dead neurons in organotypic brain slices [48] , [49] , or pooled for immunoblot analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Excessive calpain activation is strongly implicated in neurodegeneration after excitotoxic injury and SCI. 1,[28][29][30] Although small molecule calpain inhibitors protect against the neurodegeneration, 2,5,6,31-33 most calpain inhibitors are non-specific and also inhibit cysteine cathepsins such as cathepsin B and other proteases. 11,34,35 The only specific inhibitor of classical calpains is calpastatin.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the concept of apoptosis in the central nervous system has been introduced to explain the process of ischemia and trauma. Also, it has been found that some neurons and glial cells are apoptotic following SCI ( 10 , 14 , 15 ). In addition, the overstimulation of glutamate receptors is toxic to neurons and glial cells and is involved in processes culminating in programmed cell death ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%